Effectiveness of Coupled Application of AmpFℓSTR Yfiler Kit and Reduced Size Y‐chromosomal Short Tandem Repeat Analysis for Archeological Human Bones1. Issue 2 (16th September 2015) - Oh, Chang Seok; Lee, Soong Deok; Shin, Kyoung‐Jin; Shin, Dong Hoon
Abstract: The AmpFℓSTR Yfiler PCR Amplification (Yfiler) kit continues to be improved for a better analytical efficiency in cases of highly degraded DNA. The authors endeavored to determine whether coupling of the Yfiler kit with supplemental multiplex amplification of some Y‐STR loci is a more efficient analytical mode for poorly preserved human femurs ( n = 15) discovered at Korean archeological sites. To reveal locus profiles not easily obtained by Yfiler analysis, custom‐designed primers were adopted for the DYS390, DYS391, DYS392, DYS438, DYS439, and DYS635 loci. The success rate for 16 Y‐STR locus profiles obtained from the 15 femurs was improved from 18.33% (in the use of Yfiler kit only) to 49.17% (the coupled use of Yfiler and custom‐designed primers). In this study, the authors established that the custom‐designed primers offer a markedly improved success rate for obtainment of Y‐STR profiles from degraded aDNA not easily identified by sole use of the Yfiler assay.